Investigation of chemical resistance of polyurethane elastomers extended with 2,2'-tiobisethanol or 1,4-butanediol - Doczekalska, B. (Polimery, 2022)
Polyurethane (PUR) elastomers of 4,4'-diphenylmethane diisocyanate (MDI) and oligokaprolactanol (CAPA 225) have been synthesized with use of 2,2'-tiobisethanol (T) or 1,4-butanediol (B) as chain extenders. Chemical resistance of PUR elastomers to distilled water, aqueous solutions of acids, alkalis and salts (Table 1) as well as to organic solvents, hydraulic fluid or machine oil (Table 2) during 7, 14, 21, 28, 42, 56 or 70 days has been tested. It was found that hydrolytic stability of the samples in water or aqueous solutions of acids, alkalis and salts is satisfactory and adsorption did not exceed 5 % during 70 days of test period. Degradation of both PUR elastomers in 10 % solution of HNO3 has been observed after 7 days of tests. Solubility of polymers in the organic solvents, hydraulic fluid or machine oil used is good so chemical resistance of PUR elastomers is disappointing. Solubility can be ordered as follows: cyclohexanone, DMF, toluene, ethyl acetate, butyl acetate, xylene, acetone, hydraulic fluid, ethanol, and machine oil. Activity of these solvents in case of elastomer T is nearly twice higher than in case of elastomer B. Swelling of polymers occurs already after 7 days.